Coloured dissolved organic matter in a coastal arctic environment and the implications for dissolved organic carbon monitoring from Sentinel-2 MSI - Aguilar Vega, Ximena; Jiang, Dalin; Fransson, Agneta; Chierici, Melissa; Iriarte, Jose Luis; Kristoffersen, Arne; Cárdenas, Carlos; Spyrakos, Evangelos (Frontiers in Remote Sensing, 2026)
This study presents a rare, high-quality dataset of bio-geo-optical properties from an Arctic glacio-marine fjord (Kongsfjorden, Svalbard), collected during the critical spring melt and sea-ice transition period (April 2023). To our knowledge, this is the first study to utilise Sentinel-2 MSI to retrieve coloured dissolved organic matter (CDOM) and DOC in such an optically complex, high-latitude nearshore ecosystem during this season. Our findings directly address persistent challenges in Arctic remote sensing (RS). We first characterised the system’s bio-geo-optical properties, identifying CDOM as the primary light-absorbing constituent. We then demonstrated that existing atmospheric correction models (ACOLITE, C2RCC, POLYMER) perform poorly over this area, showing large errors. To overcome this, we established a regionally tuned empirical algorithm using Sentinel-2 MSI Rrs bands (490, 560, 665, and 704 nm) that provides accurate estimations of CDOM absorption (aCDOM (443)) from both in-situ and MSI data. Furthermore, we established new relationships between CDOM and DOC using our in-situ data. Applying these to MSI imagery revealed spatio-temporal dynamics: higher DOC concentrations characterised the outer fjord in spring, contrasting with higher concentrations observed at the inner-fjord glacial terminus in summer. This contribution provides a validated methodology and crucial recommendations for the RS of carbon in optically complex Arctic nearshore environments.